Otonomi Propinsi dan Kabupaten Demi Keberlanjutan Republik Indonesia? Renungan Sekali Lagi - Samodra Wibawa (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2002)
The planned and centralized development (pembangunan) in Indonesia has been already revised through free, democratic and decentralized one. This s is the right choice and should be maintained, because only this canguarantee the sustainability of the development (perkembangan) of Republic Indonesia. The new modus of government should be however accompanied however accompanied by strengthening the civil society (mass media, people organizations. intellectual associations, law enforcement!, administrative transparency etc.). Furthermore all actors at the levels of state, province as well as leabupaten should begin to learn to practise the so called Subsidiaritats- and Solidaritatprinz0 of governance.